Lactate-Dependent Regulation of Immune Responses by Dendritic Cells and Macrophages - Manoharan, Indumathi; Prasad, Puttur D.; Thangaraju, Muthusamy; Manicassamy, Santhakumar (Frontiers in Immunology, 2021)
For decades, lactate has been considered as innocuous bystander metabolite of cellular metabolism. However, emerging studies show that lactate acts as a complex immunomodulatory molecule that controls innate and adaptive immune cells' effector functions. Recent advances point to lactate as an essential and novel signaling molecule involved in shaping immune responses in the intestine and systemic sites. Here, we review these recent advances in the context of the pleiotropic effects of lactate in regulating diverse biological processes.